About Those Who Set Off to Learn about Fear - Lasoń-Kochańska, Grażyna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2017)
Review: Katarzyna Slany, Groza w literaturze dziecięcej. Od Grimmów do Gaimana, Kraków 2016